THE EFFECT OF THE COMBINATION OF BACK ACCUSED THERAPY AND CINNAMON BARK DECOCTION ON FASTING BLOOD SUGAR LEVELS IN PATIENTS WITH DIABETES MELLITUS TYPE II - I Gede Panji Santika; Mardiyono - (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Diabetes mellitus is a degenerative disease that occurs due to chronic metabolic disorders because the pancreas is not enough to produce insulin or the body cannot use the insulin that is produced optimally and effectively. Alternative treatment for type II diabetes mellitus patients with complementary therapy, a combination of back acupressure and cinnamon bark decoction in improving fasting blood sugar levels. This study was conducted to prove the effect of a combination of back acupressure therapy and cinnamon decoction on fasting blood levels in type II diabetes patients. This research is one of a kind true experimental with a plan pretest-posttest control group design. The total sample of 56 people was divided into 2 groups, each consisting of 28 respondents in the intervention group who were given back acupressure and cinnamon bark decoction, while 28 respondents in the control group were only given 5 pillars of diabetes mellitus treatment for 21 days. Then measurements of fasting blood sugar levels were carried out on the 8th and 21st days. Data tested using independent t-test. There was a decrease in blood pressure before and after treatment, namely 172.25 mg/dl to 137.07 mg/dl with a difference of 63.45 mg/dl in the intervention group, then 167.75 mg/dl to 154.96 mg/dl with a difference 76.33 mg/dl in the control group. Test results independent t-test showed a difference in decreasing fasting blood sugar levels between the intervention group and the control group with a p value of 0.000. Conclusion, giving a combination of acupressure and cinnamon bark decoction for 21 days is effective in reducing fasting blood sugar levels in patients with type II diabetes mellitus.